Non-destructive sampling of larval amphibians shows tail tissues reflect whole-body methylmercury concentrations and trophic-related differences in bioaccumulation - Brian J. Tornabene; Blake R. Hossack; Daniel A. Grear; Thomas L. Anderson; Brad M. Glorioso; J. Hardin Waddle; Jon M. Davenport; Collin A. Eagles-Smith; Caitlin T. Rumrill; Kelly L. Smalling (Ecotoxicology, 2026)
Mercury (Hg), and specifically methylmercury (MeHg), is a contaminant of global concern to humans and wildlife, but there is still limited understanding of its effects on many taxa. Amphibians are closely associated with water, where Hg is converted to MeHg, and high concentrations of MeHg can reduce survival of amphibians in the wild. However, limited non-lethal proxies exist for estimating MeHg bioaccumulation in amphibian larvae, which could be used to reduce destructive sampling and allow sampling of imperiled species. We evaluated whether tail clips were indicative of whole-body MeHg concentrations of larval amphibians, whether dragonflies were an effective bioindicator of Hg concentrations of larval amphibians, and compared MeHg bioaccumulation in predatory caudate (salamanders, newts) and non-predatory anuran (frogs, toads) larvae. Tail-clip and whole-body MeHg concentrations were strongly correlated, especially for caudates. There was high variability among sites and species, but caudates had higher MeHg than anurans, and MeHg concentrations of caudates and anurans were strongly correlated. Dragonflies were a weak indicator of MeHg for anurans but strong indicators for larval caudates, likely because caudates and dragonflies are carnivorous and occupy similar trophic positions. Our study revealed that sampling tails can be an effective non-destructive index of whole-body MeHg for larval amphibians and demonstrates differences in MeHg bioaccumulation related to trophic position in larval amphibians and dragonflies. All post-embryo life stages for a broad suite of amphibian species can now be sampled non-lethally for MeHg, allowing for a broader examination of population-level effects and focus on imperiled species that cannot be sampled destructively.

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Invasive predatory fish occupies highest trophic position leading to expansion of isotopic niches in a riverine food web - Olivia C. Hodgson; Sydney Stark; Megan K. Schall; Geoffrey D. Smith; Kelly L. Smalling; Tyler Wagner (Ecology, 2025)
Invasive species are drivers of ecological change with the potential to reshape the structure and function of terrestrial and aquatic ecosystems. The invasive flathead catfish ( Pylodictis olivaris ) is an opportunistic predator that has established a rapidly growing population in the Susquehanna River, Pennsylvania, USA, since they were first detected in 2002. Although the predatory effects of invasive catfishes on native fish communities have been documented, the effects of invasion on riverine food webs are poorly understood. This study quantified the effects of invasive flathead catfish on the trophic position (TP) and isotopic niche of the river's food web by comparing invaded and non‐invaded sites. In addition to flathead catfish, the food web components examined included crayfish, minnows, and two ecologically and socioeconomically important fish species: the smallmouth bass ( Micropterus dolomieu ) and channel catfish ( Ictalurus punctatus ). We found that flathead catfish occupied the highest TP, with a posterior mean TP of 3.08 (95% credible interval = [2.71, 3.42]), exceeding that of the two resident fish predators, the smallmouth bass and channel catfish. The TP of the resident channel catfish, which occupies a similar ecological niche, declined after flathead catfish invasion. In fact, there was a 0.92 posterior probability that channel catfish TP was lower in invaded sites than at non‐invaded sites. Using a Bayesian bivariate ellipses analysis, we found overwhelming evidence of isotopic niche expansion and overlap for all components of the food web in the presence of flathead catfish. These findings support the “trophic disruption hypothesis,” where an introduced species prompts resident species to change diets in an attempt to avoid competition and predation following invasion. Our results indicate that flathead catfish invasion is altering food web structure and energy flow in a large riverine ecosystem and contributes to the breadth of knowledge regarding how ecosystems may respond to the introduction of a large predatory fish species.

Deformity, erosion, lesion, tumor, and parasite (DELT) anomalies in fish communities of the Chesapeake Bay watershed, USA: a regional assessment and potential landscape drivers - Sara E. Breitmeyer; Paul McLaughlin; Vicki S. Blazer; Gregory B. Noe; Kelly L. Smalling; Timothy Wertz; Tyler Wagner (Environmental Monitoring and Assessment, 2025)
Fish diseases in freshwater ecosystems pose significant ecological and socioeconomic challenges, yet monitoring them in wild populations is complex due to interactions between pathogens, hosts, and environmental conditions. We examine the prevalence and watershed-scale landscape drivers of external deformity, erosion, lesion, tumor, and parasite (DELT) anomalies in 57 riverine fish species using a large dataset (577,266 individuals collected 2008–2019) from the Chesapeake Bay watershed that originated from state and federal agencies. Overall, DELT prevalence was low (1.4%), but was higher in larger, longer-lived species, including Channel Catfish ( Ictalurus punctatus ) (18.9%), Rock Bass ( Ambloplites rupestris ) (7.6%), Smallmouth Bass ( Micropterus dolomieu ) (7.3%), Brown Bullhead ( Ameiurus nebulosus ) (5.6%), and Yellow Bullhead ( Ameiurus natalis ) (5.1%), signifying their potential as regional environmental health indicators. Spatial analysis indicated warmer temperatures increased the estimated probability of DELT occurrence, whereas higher precipitation often mitigated the probability of DELT occurrence. Conservation strategies (e.g., best management practices) had mixed effectiveness in reducing DELT occurrence probability across agricultural and urban landscapes. Across the landscape, various drivers, including harvested forest, impervious land, and pesticide use, influenced DELT occurrence probability differently across species. However, uncertainty remains partly due to low prevalence and variability in sampling methods across agencies. Despite low overall prevalence, DELT occurrence is a rapid fish health indicator. Future research could emphasize species-specific responses and longitudinal studies that incorporate life stages and health indicators. Understanding these intricate, multi-scale interactions is vital for effective monitoring, conservation, and adaptive management of freshwater ecosystems. Graphical abstract

Statewide cumulative human health risk assessment of inorganics-contaminated groundwater wells, Montana, USA - Margaret J. Eggers; W. Adam Sigler; Nicklas Kiekover; Paul M. Bradley; Kelly L. Smalling; Albert Parker; Robert K.D. Peterson; John I. LaFave (Environmental Pollution, 2025)

Mixed contaminant exposure in tapwater and the potential implications for human-health in disadvantaged communities in California - Kelly L. Smalling; Kristin M. Romanok; Paul M. Bradley; Michelle L. Hladik; James L. Gray; Leslie K. Kanagy; R. Blaine McCleskey; Diana A. Stavreva; Annika K. Alexander-Ozinskas; Jesus Alonso; Wendy Avila; Sara E. Breitmeyer; et al. (Water Research, 2024)

Temporal concentrations of Quaternary ammonium compounds in wastewater treatment effluents during the COVID-19 pandemic, 2020–2021 - Michelle L. Hladik; Michael S. Gross; Gabrielle P. Black; Dana W. Kolpin; Jason R. Masoner; Patrick J. Phillips; Paul M. Bradley; Kelly L. Smalling (Chemosphere, 2024)

Per- and polyfluoroalkyl substances (PFAS) in drinking water in Southeast Los Angeles: Industrial legacy and environmental justice - Julie Von Behren; Peggy Reynolds; Paul M. Bradley; James L. Gray; Dana W. Kolpin; Kristin M. Romanok; Kelly L. Smalling; Catherine Carpenter; Wendy Avila; Andria Ventura; Paul B. English; Rena R. Jones; et al. (Science of The Total Environment, 2024)

Tire-derived contaminants 6PPD and 6PPD-Q: Analysis, sample handling, and reconnaissance of United States stream exposures - Rachael F. Lane; Kelly L. Smalling; Paul M. Bradley; Justin B. Greer; Stephanie E. Gordon; John D. Hansen; Dana W. Kolpin; Andrew R. Spanjer; Jason R. Masoner (Chemosphere, 2024)

A brief note on substantial sub-daily arsenic variability in pumping drinking-water wells in New Hampshire - Paul M. Bradley; Emily C. Hicks; Joseph P. Levitt; David C. Lloyd; Mhairi M. McDonald; Kristin M. Romanok; Kelly L. Smalling; Joseph D. Ayotte (Science of The Total Environment, 2024)

Energy-related wastewater contamination alters microbial communities of sediment, water, and amphibian skin - Brian J. Tornabene; Kelly L. Smalling; Carrie E. Givens; Emily B. Oja; Blake R. Hossack (Science of The Total Environment, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Restored Agricultural Wetlands in central Iowa: Habitat Quality and Amphibian Response - Rebecca A. Reeves; Clay L. Pierce; Kelly L. Smalling; Robert W. Klaver; Mark W. Vandever; William A. Battaglin; Erin Muths (Wetlands, 2016)

A Multi-residue Method for the Analysis of Pesticides and Pesticide Degradates in Water Using HLB Solid-phase Extraction and Gas Chromatography–Ion Trap Mass Spectrometry - Michelle L. Hladik; Kelly L. Smalling; Kathryn M. Kuivila (Bulletin of Environmental Contamination and Toxicology, 2008)